PHILOSOPHICAL SIGNIFICANCE OF CORPUSCULAR AND WAVE DUALISM IN DEVELOPMENT OF A NATURE AND N. BOR׳S PRINCIPLE OF «COMPLEMENTARITY» AT IT’S RESEARCH - Лагетко, В. В. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
The opening of an electron with i’ts corpuscular and wave dualism has spotted it as an intermediate in continuons development of a nature. In it it’s philosophical value for a science and N. Bor׳s principle of «complementarity» at it’s research.